2016
DOI: 10.1021/acs.jpcb.6b06151
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Induced Changes in the Protein Environment and Site Energies in the (M)L214G Mutant of the Rhodobacter sphaeroides Bacterial Reaction Center

Abstract: This work focuses on the low-temperature (5 K) photochemical (transient) hole-burned (HB) spectra within the P870 absorption band, and their theoretical analysis, for the (M)L214G mutant of the photosynthetic Rhodobacter sphaeroides bacterial reaction center (bRC). To provide insight into system-bath interactions of the bacteriochlorophyll a (BChl a) special pair, i.e., P870, in the mutated bRC, the optical line shape function for the P870 band is calculated numerically. On the basis of the modeling studies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…There have been several computational studies targeting BRC systems ,,, including studies focusing on the Q y spectra , of the core pigments as the BChl monomer and BChl dimers. However, open questions regarding these bands remain. For example, a proper characterization of the blue-shifted P state is required to investigate its role in capturing the excitation energy as hypothesized by earlier studies. , The actual spectral splitting in the P bands is difficult to resolve since the blue-shifted state is a dark state that eludes spectral studies. Other spectral trends related to the BChl pair and the BPhe pair are also challenging full understanding, where the B A state is blue-shifted over that of B B , whereas a red-shift is indicated for the H A state over the H B one. …”
Section: Introductionmentioning
confidence: 99%
“…There have been several computational studies targeting BRC systems ,,, including studies focusing on the Q y spectra , of the core pigments as the BChl monomer and BChl dimers. However, open questions regarding these bands remain. For example, a proper characterization of the blue-shifted P state is required to investigate its role in capturing the excitation energy as hypothesized by earlier studies. , The actual spectral splitting in the P bands is difficult to resolve since the blue-shifted state is a dark state that eludes spectral studies. Other spectral trends related to the BChl pair and the BPhe pair are also challenging full understanding, where the B A state is blue-shifted over that of B B , whereas a red-shift is indicated for the H A state over the H B one. …”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that (M)­L214G mutation in the WT bacterial reaction center (bRC) modified the total electron–phonon coupling strength of the special pair BChl a and significantly increased inhomogeneous broadening . A presence of different subpopulations was also observed in the (M)­L214G mutant, where after mutation a large fraction (∼50%) of the H A chromophores shifted red (with the significantly broadened absorption band), while the remaining fraction of H A cofactors remained nearly the same site energy as H A in WT bRC . The latter, however, did not affect the electron transfer time in the (M)­L214G mutant, which was similar to that observed in the WT bRC (∼1 ps), though the quantum efficiency of P + Q A – state formation in the mutant has been altered.…”
mentioning
confidence: 99%
“…For example, it was demonstrated that a small alteration in the local structure of the Escherichia coli cyclic AMP receptor protein (CRP), via amino acid substitution, dramatically changes overall protein dynamics, which plays an important role in modulating the allosteric behavior of CRP . It was also shown that (M)­L214G mutation in the WT bacterial reaction center (bRC) modified the total electron–phonon coupling strength of the special pair BChl a and significantly increased inhomogeneous broadening . A presence of different subpopulations was also observed in the (M)­L214G mutant, where after mutation a large fraction (∼50%) of the H A chromophores shifted red (with the significantly broadened absorption band), while the remaining fraction of H A cofactors remained nearly the same site energy as H A in WT bRC .…”
mentioning
confidence: 99%
“…The spectral density C()ω in Equations (), and () can have any physically plausible form that suits the conditions of the experiment or the model at hand and certainly is not limited to Equation (). For example, besides the spectral density of the Brownian oscillator model shown in Equation (), the spectral density of Fleming, 39 Mayer, 23,40 Toutounji, 17 or the spectral density proposed by Jankowiak, 20–22 Renger, 24,25 or Rätsep 26 in photosynthetic complexes may undoubtedly be employed, depending on the conditions and the parameters of the problem at hand. A vitally important relationship (widely used in the Brownian oscillator model) that embodies the molecular motion of the surrounding environment in the electronic transition dipole moment time correlation functions is J()t=exp{}[]0titalicds0sitalicdτ〈〉q()τq()0, of which the Fourier transform renders the linear absorption line shape function.…”
Section: Non‐condon Spectroscopy Using Distribution Functionmentioning
confidence: 99%
“…For example, the bath spectral density may be employed to evaluate temporal average values (e.g., time correlation functions) with the aid of the fluctuation‐dissipation theorem 17–19 . Utilizing the spectral density in evaluating the transition dipole moment correlation function will allow encompassing many cases and conditions to probe dynamical effects using the appropriate experimental or theoretical spectral density 17–27 . While the bath spectral density approach has been a popular tool to study the aforementioned correlation functions, and therefore the electronic excited state dynamics when coupled to lattice vibrations (phonons), this article will introduce a novel method that is capable of probing the excited vibronic state and the consequential spectral dynamics.…”
Section: Introductionmentioning
confidence: 99%